2019
DOI: 10.1128/iai.00655-18
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Cross-Sectional Studies on the Genesis of Hypoargininemia in Severe Pediatric Plasmodium falciparum Malaria

Abstract: The low bioavailability of nitric oxide (NO) and its precursor, arginine, contributes to the microvascular pathophysiology of severe falciparum malaria. To better characterize the mechanisms underlying hypoargininemia in severe malaria, we measured the plasma concentrations of amino acids involved in de novo arginine synthesis in children with uncomplicated falciparum malaria (UM; n ϭ 61), children with cerebral falciparum malaria (CM; n ϭ 45), and healthy children (HC; n ϭ 109). We also administered primed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 58 publications
3
17
0
Order By: Relevance
“…A significant depletion of amino acids occurs in the bloodstream of Plasmodium-infected hosts, and a number of studies have characterized these perturbations [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Of these, arginine, glutamine, and tryptophan have received the most attention in recent studies due to the direct clinical consequences when either are decreased.…”
Section: Bloodstream Amino Acid and Glucose Perturbations In Malariamentioning
confidence: 99%
See 2 more Smart Citations
“…A significant depletion of amino acids occurs in the bloodstream of Plasmodium-infected hosts, and a number of studies have characterized these perturbations [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Of these, arginine, glutamine, and tryptophan have received the most attention in recent studies due to the direct clinical consequences when either are decreased.…”
Section: Bloodstream Amino Acid and Glucose Perturbations In Malariamentioning
confidence: 99%
“…https://doi.org/10.1371/journal.ppat.1008930.g001 glutamine levels are depleted in the human host in both falciparum and vivax malaria [9,21,22,28]. In addition to impacting arginine biosynthesis ( Fig 1A), low plasma glutamine has been associated with severe malarial anemia in children with P. falciparum [29] and with impaired humoral immunity in a murine model of severe malaria [27].…”
Section: Bloodstream Amino Acid and Glucose Perturbations In Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with severe malaria show low nitric oxide (NO) bioavailability resulting in impaired microvascular function 6,7 . Low levels of the NO synthase (NOS) substrate L-arginine and of the NOS cofactor tetrahydrobiopterin are also observed 810 , as well as disruption of NOS substrate/inhibitor homeostasis, all these factors limiting NO production 11,12 . These findings prompted the proposal of L-arginine supplementation as a tool to improve vascular function in severe malaria and a number of safety and efficacy studies have been conducted in recent years 1315 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies over the last several decades have shown that nitric oxide (NO) levels are associated with protection from malarial disease [5155], and prior work has reported age-associated effects on NO metabolites during malaria infection [56]. The results presented here suggest that NO metabolite levels are upregulated in young children compared with adults, however, it is important to note that these measures did not change between V1 and V2, and they did not correlate with parasitaemia as other studies have found [57].…”
Section: Discussionmentioning
confidence: 99%